Hubungan Pengetahuan dan Sikap dengan Perilaku Pencegahan HIV/AIDS pada Siswa Kelas VIII.1 SMPI Darul Mu’minin Bekasi - Nurfadillah, Nurfadillah; Indawati, Eli (Universitas Malahayati, 2025)
ABSTRACT WHO identified HIV as a global health issue that resulted in the loss of 40.4 million lives, in the African region around 630 thousand died due to HIV. According to UNICEF, in 2022, as many as 480 thousand teenagers will be newly infected with HIV, including teenagers aged 10-24 years. In Indonesia, HIV/AIDS is recorded in 433 of 514 districts/cities in 34 provinces covering around 84.2%. According to a report from the Bekasi City Health Office, there were 554 HIV cases reported in the period January-August 2024 with ages 25-49 years (113 people), over 50 years (44 people), ages 15-19 years (14 people), and children under age 4 years (4 cases).To determine the relationship between knowledge and attitudes and HIV/AIDS prevention behavior among students at SMPI Darul Mu'minin Bekasi. Correlation method with a cross sectional approach collected using a questionnaire with a sample size of 52 respondents. Of the 52 respondents, 10 people (17.3%) had low knowledge, 7 people (11.5%) had poor attitudes, and 27 people (51.9%) had sufficient preventive behavior. There was no relationship between HIV/AIDS knowledge and HIV/AIDS prevention behavior (P value = 0.141), and there was no relationship between attitudes and HIV/AIDS prevention behavior (P value = 0.862).Most students understand HIV/AIDS. Overall, students' attitudes towards HIV/AIDS prevention look good, although there are still several aspects that need to be improved to encourage them to take preventive action. Therefore, increasing education about HIV/AIDS and forming positive attitudes must be a top priority in efforts to increase preventive behavior among adolescents. Keywords: Knowledge, Attitudes, Behavior, Prevention, HIV/AIDS ABSTRAK WHO mengungkapkan HIV sebagai isu kesehatan global yang mengakibatkan kehilangan 40,4 juta nyawa, di wilayah Afrika sekitar 630 ribu meninggal akibat HIV. Menurut UNICEF pada tahun 2022 banyak remaja yang baru tertular HIV yaitu sebanyak 480 ribu diantaranya remaja berusia 10-24 tahun. Di Indonesia HIV/AIDS tercatat di 433 dari 514 kabupaten/kota di 34 provinsi mencakup sekitar 84,2%. Menurut laporan Dinkes Kota Bekasi terdapat 554 kasus HIV yang dilaporkan dalam rentang waktu januari-Agustus 2024 dengan usia 25-49 tahun (113 orang), diatas 50 tahun (44 orang), usia 15-19 tahun (14 orang), dan anak dibawah usia 4 tahun (4 kasus). Mengetahui hubungan pengetahuan dan sikap dengan perilaku pencegahan HIV/AIDS pada siswa SMPI Darul Mu’minin Bekasi. Metode kolerasi dengan pendekatan cross sectional yang dikumpulkan dengan kuesioner dengan jumlah sampel sebanyak 52 responden. Dari 52 responden yang memiliki pengetahuan rendah sebanyak 10 orang (17,3%), yang memiliki sikap kurang sebanyak 7 orang (11,5%), dan yang memiliki perilaku pencegahan yang cukup sebanyak 27 orang (51,9%). Tidak terdapat hubungan antara pengetahuan HIV/AIDS dengan perilaku pencegahan HIV/AIDS (P value = 0,141), serta tidak adanya hubungan antara sikap dengan perilaku pencegahan HIV/AIDS (P value = 0,862). Sebagian besar siswa memahami HIV/AIDS. Secara keseluruhan sikap siswa terhadap pencegahan HIV/AIDS terlihat baik meskipun demikian, masih ada beberapa aspek yang perlu di perbaiki mendorong mereka untuk mengambil tindakan pencegahan. Oleh karena itu, peningkatan pendidikan mengenai HIV/AIDS dan pembentukan sikap yang positif harus menjadi prioritas utama dalam upaya meningkatkan perilaku pencegahan di kalangan remaja. Kata Kunci: Pengetahuan, Sikap, Perilaku, Pencegahan, HIV/AIDS